2015
DOI: 10.1088/1475-7516/2015/08/028
|View full text |Cite
|
Sign up to set email alerts
|

Weak lensing by voids in modified lensing potentials

Abstract: We study lensing by voids in Cubic Galileon and Nonlocal gravity cosmologies, which are examples of theories of gravity that modify the lensing potential. We find voids in the dark matter and halo density fields of N-body simulations and compute their lensing signal analytically from the void density profiles, which we show are well fit by a simple analytical formula. In the Cubic Galileon model, the modifications to gravity inside voids are not screened and they approximately double the size of the lensing ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 138 publications
(300 reference statements)
2
136
0
Order By: Relevance
“…those with the chameleon screening mechanism, voids are expected to be emptier than their GR counterparts. The dark matter profile of voids can therefore provide powerful test for modified gravity (Clampitt, Cai & Li 2013;Barreira et al 2015;Cai, Padilla & Li 2015;Lam et al 2015). Our measurement suggests that it is possible to do this with CMB lensing.…”
Section: S U M M a Ry A N D C O N C L U S I O N Smentioning
confidence: 74%
“…those with the chameleon screening mechanism, voids are expected to be emptier than their GR counterparts. The dark matter profile of voids can therefore provide powerful test for modified gravity (Clampitt, Cai & Li 2013;Barreira et al 2015;Cai, Padilla & Li 2015;Lam et al 2015). Our measurement suggests that it is possible to do this with CMB lensing.…”
Section: S U M M a Ry A N D C O N C L U S I O N Smentioning
confidence: 74%
“…Barreira et al (2015) have shown Galileon models have a large effect on void lensing predictions. It would be interesting to test whether such theories also give significantly different results for void bias.…”
Section: Discussionmentioning
confidence: 99%
“…(6) the "RR" model. Further work on the RR and RT models has been presented in [51][52][53][54][55][56][57][58][59].…”
Section: An Overview Of Nonlocal Modelsmentioning
confidence: 99%